THE INFLUENCE OF CONTEXTUAL MODELS ON PROCESSING SKILLS AND SCIENCE CONCEPT MASTERY IN SD 207 JAMBI CITY - Tukarmi Tukarmi; Hadiyanto Hadiyanto; Ugi Nugraha (Institute of Computer Science (IOCS), 2022)
This study aims to see how science process skills and student learning outcomes apply a contextual learning approach in science learning. The method used is a quasi-experimental using a control class and an experimental class for fifth grade students at SD Negeri 207 Jambi City. Collecting data by giving 25 multiple choice questions. The data analysis technique used normality test, SPSS 25 homogeneity test and T-test. The results showed that there was a positive effect in the